The Important Place of Indonesia in the Formation of International Culture Today - Martha C. Beck (Sunan Kalijaga: International Journal of Islamic Civilization, 2019)
This paper begins with excerpts from Ervin Lazlo’s book, The Systems View of the World, one version of the emerging paradigm for understanding the universe, the natural world, the human psyche and human culture. The second section presents excerpts from Antonio Damasio’s book, Looking for Spinoza: Joy, Sorrow and the Feeling Brain. Damasio is a highly respected neuroscientist whose discoveries about the inner mapping of the human brain have led him to reject Enlightenment views of human psychology and replace them with another version of Lazlo’s “systems” approach. The third section presents Indonesia’s Pancasila, a five-point political ideology that serves as the foundation for their democratic republic. This ideology begins with the belief in God, but the notion of “God” is one more example of a type of “systems” thought. The fourth section includes an interview from Dr. Amad Kardimin, professor of education at Sunan Kalijaga Islamic State University in Yogyakarta, Indonesia. Dr. Kardimin describes the beliefs and way of living in the small village where he grew up. I will interpret what he says in light of my own scholarship about Aristotle’s model of the flourishing human life, a life of both practical and theoretical wisdom. Even though the people in this village are not formally educated, they are living much more wisely than many highly respected intellectuals today. Finally, I will quote from a number of public intellectuals in the United States who are very worried about the decline in quality of life in the United States today. This decline will lead to an increase in authoritarianism in the U.S. I conclude that too many developing nations have looked to the West, especially the United States, for guidelines about how to “move forward.” Their best and brightest young people are sent to Western universities and go back home to educate their own best and brightest to think and act like Westerners. This is a mistake. Indonesia is continually working on a model of education that unites the moral with the intellectual virtues. The West, especially the United States, has focused on higher and higher levels of education in science, math, and computer science without adequate concern for avoiding greed, pride, power hunger and other vices. Indonesia and other developing nations should recognize the importance of an education for wisdom. Leaders in all sectors should exhibit both moral and intellectual excellence. The future of international culture, politics and even of life on earth is at stake.